Axial compressive behaviour of GFRP tube reinforced concrete columns. (15th April 2015) - Hadi, Muhammad N.S.; Wang, Weiqiang; Sheikh, M. Neaz
Highlights: GFRP tube is used as reinforcement for FRP tube reinforced concrete (FTRC) columns. Perforated GFRP tubes integrate concrete core with concrete cover. GFRP tube improves the strength and the ductility capacity of FTRC columns. Influence of tube perforation on the behaviour of FTRC columns is numerically assessed. Abstract: This paper presents an innovative reinforcing scheme for concrete columns using glass fibre reinforced polymer (GFRP) tubes. GFRP tubes (solid and perforated) have been placed into concrete columns to provide reinforcement in both longitudinal and transverse directions. In this study, 14 columns with 150 mm diameter and 300 mm height have been cast and tested under axial compression. The columns have been divided into seven groups; each group contains two columns. The first group of columns are the reference columns without any reinforcement. The other six groups of columns are reinforced with solid and perforated (axially and diagonally) GFRP tubes. The test results show that GFRP tubes are effective in improving the strength and the ductility capacity of FRP (fibre reinforced polymer) tube reinforced concrete (FTRC) columns. Also, perforated GFRP tubes have been found effective in integrating concrete core with concrete cover. However, axially perforated FTRC columns have been found most effective considering the strength and the ductility capacity of the concrete columns. In addition to the experimental investigations, numerical simulations have been carried out to assess the influence of tube perforations on the behaviour of FTRC columns. The simulation results show that reduction in the hole diameter, rather than increase in the vertical hole spacing, is the most effective in increasing the strength and the ductility capacity of FTRC columns.